GROWTH AFTER ADVERSITY: The Lived Experiences of Posttraumatic Growth Among Selected Covid-19 Survivors in Bataan, Philippines - Redge Ainne Labios; Angela Dela Cruz; Jayvie Villazor; Ieleen Academia (Camarines Sur Polytechnic Colleges, 2024)
Dealing with a traumatic event, such as severe COVID-19 symptoms, may deplete one's strength and fill them with fear and hopelessness. Despite such events that may demoralize an individual, the Posttraumatic Growth (PTG) phenomenon allows for the possibility of growth in the face of adversity. The purpose of this study is to explore the lived experiences of Posttraumatic Growth of the COVID-19 survivors and to ascertain what aspects of positive growth they have experienced. The researchers used purposive sampling to obtain the required number of respondents and used the interview protocol to conduct a semi-structured interview to gather the necessary information. Five themes have been identified using Colaizzi's seven steps for descriptive phenomenological data analysis. Specifically; (1) savor, (2) invigorating, (3) benevolent, (4) optimistic, and (5) light, which then abbreviated as SIBOL, a Tagalog word which means sprout; growth; spring that symbolizes the beginning of the growth of COVID-19 survivors. They perceived the Posttraumatic Growth as an opportunity to live their lives differently, this time embracing the new positive changes in their lives. Though there have only been a few studies on Posttraumatic Growth in the Philippines, it has the potential to raise a lot of awareness about the possible benefits of attaining Posttraumatic Growth. This assists in identifying a way to view adversity as a challenge that will aid in the growth process, where our emphasis shifts from learning about negative experiences to facilitating Posttraumatic Growth itself.